Seminar on Stochastic Analysis, Random Fields, and Applications III : Centro Stefano Franscini, Ascona, September 1999 - Seminar on Stochastic Analysis, Random Fields, and Applications (3rd : 1999 : Ascona, Switzerland); Dalang, Robert C., 1961-; Dozzi, M.; Russo, Francesco, 1959- (Basel : Birkhauser, 2002)
41